Pemanfaatan Limbah Oli Bekas Sebagai Bahan Bakar Alternatif Untuk Kompor Bertekanan Udara - Umami, Mahrus Khoirul; Irawan, Ibnu; Alim, Wildan; Arifin, Zainal (Universitas Negeri Gorontalo, 2025)
As the number of vehicles increases, the amount of used oil waste also increases. Used oil waste can be used as an alternative fuel energy for stoves. In the combustion process of used oil, the mixture of air and fuel can affect the achievement of optimal temperature by applying the right AFR (Air Fuel Ratio). The chemical formula of used oil can be known using the GC-MS (Gas Chromatography-Mass Spectrometry) test. The purpose of this study is to calculate the stoichiometric AFR, determine the resulting combustion temperature, then the combustion time at each variation of air mass rate of 0.00193 kg/s, 0.00276 kg/s, 0.00359 kg/s, 0.00442 kg/s and 0.00525 kg/s. The results of the GC-MS test of used oil obtained the chemical formula C22H46, so the stoichiometric AFR is 14.8:1. Stoichiometric combustion occurs at an air mass rate of 0.00359 kg/s producing a flame temperature of 876.8°C and a furnace temperature of 535.2°C, with a combustion duration of 1627 seconds, producing a blue flame across the furnace surface as an indicator of low emission values ​​and no soot. The combustion value with the highest temperature occurs at an air mass rate of 0.00525 kg/s, namely 1124°C, on the flame and 694.6°C on the furnace with a combustion duration of 1229 seconds. The lowest temperature occurs at a mass rate of 0.00193 kg/s, namely 767.5°C on the flame and 290.8°C on the furnace with a combustion duration of 2224 seconds. This study can be concluded that the greater the air mass rate, the higher the combustion temperature value so that the combustion is faster. This used oil stove can be an alternative new technology, which can replace people's dependence on gas stoves and become a solution for environmentally friendly stoves that do not emit soot in their combustion.